Five Years a Dragoon (‘49 to ‘54) and other Adventures on the Great Plains - Percival G. Lowe (Symphony in the Flint Hills, 2013)
Excerpt from "Five Years a Dragoon," detailing exploration and wagon travel.
Keywords: dragoon; Fort Leavenworth; army; military; Thomas T. Fauntleroy; troops; soldiers; Fort Union; New Mexico; Cimarron Crossing; Arkansas; exploration; explore; mules; oxen; wagon; Lieutenant Hastings